Painless complex regional pain syndrome: a paradoxical case report - Arefyeva, A. P.; Seliverstova, E. G.; Sinkin, M. V. (Frontiers in Musculoskeletal Disorders, 2025)
ObjectiveWe present a case of a condition that is most likely to be complex regional pain syndrome (CRPS) type 1 in a young male patient with an atypical presentation.Case descriptionA 32-year-old male patient admitted to the outpatient department reported slow progressive complaints that included foot weakness, abnormal posture, edema, and temperature and skin discoloration of the affected leg. A wide range of instrumental studies revealed little-to-no abnormalities that could explain the symptoms. Thus, the diagnosis of exclusion remains CRPS. However, the patient did not experience pain, which is necessary for the diagnosis of CRPS.DiscussionThere are several cases in the literature describing the condition that is very similar to CRPS, but without pain syndrome. Since CRPS is a rare condition, and the exact mechanisms of its pathogenesis are not fully understood. It is not possible to conclude whether these cases represent an atypical manifestation of CRPS or a similar condition with different underlying pathophysiology. CRPS should be included in the differential diagnosis in cases where all other clinical features of CRPS, except pain, are present.